Relação entre o ideal e o real: a efetivação do Projeto Ético Político do Serviço Social - Fernandes, Pedro Alves [UNESP] (2014)
The Ethical Political Project of Social Services is subject of various researches. This work is a result of these studies, conducted in the Triângulo Mineiro region. Search this developed for the Graduate Program in Social Work - as a doctoral thesis at UNESP, Franca. The research aimed to clarify and understand the limits and possibilities of insertion of Ethical Political Project of Social Work in the daily professional work of (a) a social worker of the Triângulo Mineiro region. Correlated to both the principles of design with the exercise of professional social workers, through semi-structured interview. Uberlândia, Uberaba, Patos de Minas and Ituiutaba, being a professional in every 100,000 thousand inhabitants: a sample of 11 professionals representing four cities eleven poles were interviewed . Two criteria for participation as a subject of research were established: training after the final implementation of the Curriculum Guidelines for courses in Social Work in 2002, and at least two years of professional practice. As a result we conclude that research has shown a good knowledge of Ethical Political Project of Social Work professionals working in the Triângulo Mineiro region , and that these professionals seek in their everyday practices hallmarks implement the principles of the Project using the spaces for the realization of joint of theory in professional practice